The ISO 14000 challenge [ environmental management : guide for managers - Campbell, Catherine (Nicholas and Smith, 1997)
Describes the key elements of environmental management by showing how 3 very different organisations (Bonlac Foods, MacMahon Contractors and Woollahra Council) have applied the principles of ISO 14001 in their business situations